VISÖ - Visualization of Infrastructure and Sustainable development in Öresund - Hultén, John; Schantz, Petra; Andersson, Bengt (Proceedings from the Annual Transport Conference at Aalborg University, 2011)
Sustainable growth is a shared goal and challenge for policy-makers at local, regional, national as well as European levels of government. However, due to the complexity and interplay of the driving forces it is often difficult for decision-makers to predict the lasting effects of large infrastructure investments and other significant changes to the land use structure and transport system. In cross-border regions, the difficulties facing decision-makers are even more demanding due to shortage of joint planning tools and institutions. Substantial research literature confirms the hypothesis that analysis aimed at decision-support in general has limited impact on actual decision-making. One reason might be that effects and results often are evaluated based on complex system analyses and mathematically derived formulas which are often only understood by experts. This, combined with the lack of coordinated facts, maps and tools on which alternative development scenarios are formulated and long term planning decisions are ultimately based, constitutes a considerable difficulty for decision-makers at all levels, whether politicians or civil servants. Project VISÖ - Visualization of Infrastructure and Sustainable development in Öresund is a joint Swedish and Danish research collaboration to develop a coordinated planning tool and methodology – from which alternative development scenarios and strategic infrastructure choices and their effects can be better understood, communicated and visualized in pedagogic illustrations and purposeful dialogues in a cross- border region context. The new platform will ultimate enable planning authorities, politicians and affected communities to better understand and shape decisions regarding the development within a cross-border region in a positive, smarter and greener direction. Project VISÖ is financially supported by EU Interreg IVA. Partners are the Swedish Transport Administration, the Danish Road Directorate, Region Hovedstaden, Region Själland and Region Skåne.